2007
DOI: 10.1007/s10439-007-9268-z
|View full text |Cite
|
Sign up to set email alerts
|

Context Specific Transcription Factor Prediction

Abstract: Abstract-One of the goals of systems biology is the identification of regulatory mechanisms that govern an organism's response to external stimuli. Transcription factors have been hypothesized as a major contributor to an organism's response to various outside stimuli, and a great deal of work has been done to predict the set of transcription factors which regulate a given gene. Most of the current methods seek to identify possible binding sites from genomic sequence. Initial attempts at predicting transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…For this, we designed an integrative approach of computational and experimental methods to identify the transcriptional regulators of IRG1 in mammalian macrophages, where the notion “co-expression implies co-regulation” is satisfied [ 37 ]. Transcription factors play a pivotal role in modulating gene expression and thus contribute to the overall regulation of biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…For this, we designed an integrative approach of computational and experimental methods to identify the transcriptional regulators of IRG1 in mammalian macrophages, where the notion “co-expression implies co-regulation” is satisfied [ 37 ]. Transcription factors play a pivotal role in modulating gene expression and thus contribute to the overall regulation of biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…(Note: in the analysis that follows, we assume that the base line expression levels, i.e., in the absence of the drug, are represented by mRNA and protein abundance levels prior to drug administration). In a number of previous publications, we have illustrated the analysis of longitudinal data with a time-varying base line ( Androulakis et al, 2007 ; Yang et al, 2007b , 2008a , 2009b , 2012a , b ; Yang E.H. et al, 2009 ; Almon et al, 2008a , b ; Nguyen et al, 2009 , 2010a , b , 2011 , 2014a ; Ovacik et al, 2010 ; Scheff et al, 2010a ; Swiss et al, 2011 ). However, temporal relations among time-varying quantities are known to be non-trivial, extending far beyond the classic view of correlation ( Qian et al, 2001 ).…”
Section: Data-driven Integration Of Transcriptomic and Proteomic Datamentioning
confidence: 99%
“…The diversity of the available models describing gene induction by MPL have been expanded to several pharmacogenomics models that explain the response of numerous genes with various dynamic patterns ( Almon et al, 2003 , 2005 , 2007a , b ; Jin et al, 2003 ; Nguyen et al, 2014a ). Our earlier studies in collaboration with Prof. Jusko, characterized global dynamics of the systems that are regulated by CS at the transcriptional level across multiple tissues in adrenalectomized (ADX) and intact male rats, following single and chronic dosing of MPL enabling us to: (a) develop transcription-level understanding of MPL (acute vs. chronic) effects; (b) elaborate on tissue-specific transcriptional differences; (c) assess MPL-induced dose- and tissue-specific transcriptional regulation; and (d) assess circadian dynamics and regulation of intact and MPL-dosed animals ( Yang et al, 2007b , 2008a ; Yang E.H. et al, 2009 ; Almon et al, 2008a ; Nguyen et al, 2010a , b , 2014a ; Ovacik et al, 2010 ; Scheff et al, 2010a , 2011 ).…”
Section: Data-driven Integration Of Transcriptomic and Proteomic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering of evolutionarily conserved cis -regulatory elements has been previously demonstrated for transcription factors binding sites. Recent transcription factors binding site prediction tools have demonstrated that consideration of neighboring effects dramatically improves prediction performance compared to strategies that consider only a single site [ 22 - 25 ].…”
Section: Introductionmentioning
confidence: 99%